2014
DOI: 10.7314/apjcp.2014.15.18.7897
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Non-Communicable Disease Risk Factors Among Employees at a Saudi University

Abstract: Background: There is paucity of studies defining the prevalence of non-communicable disease (NCD) risk factors in Saudi Arabia despite the surging epidemic of obesity, change in dietary habits and sedentary lifestyle. Objectives: This cross-sectional study aimed to assess the prevalence of NCDs risk factors among employees at King Faisal University in Al Hassa, Saudi Arabia and to determine the possible correlates for clustering of NCDs risk factors among them. Materials and Methods: All employees were invited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 31 publications
21
38
1
Order By: Relevance
“…According to our findings, increasing age was an important risk factor associated with DM in Bisha province, which is in agreement with other reports from other parts of Saudi Arabia (Al Hayek et al, 2014;Amin et al, 2014;Murad et al, 2014) and neighboring countries (Ahmed et al, 2013;Ali, Mehrass, Al-Adhroey, Al-Shammakh & Amran, 2016). Ammarasinghe et al (2015) proposed that geriatric changes in the body systems might invariably contribute to this association.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…According to our findings, increasing age was an important risk factor associated with DM in Bisha province, which is in agreement with other reports from other parts of Saudi Arabia (Al Hayek et al, 2014;Amin et al, 2014;Murad et al, 2014) and neighboring countries (Ahmed et al, 2013;Ali, Mehrass, Al-Adhroey, Al-Shammakh & Amran, 2016). Ammarasinghe et al (2015) proposed that geriatric changes in the body systems might invariably contribute to this association.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, with increasing age, adipose deposition could be increased which might lead to insulin resistance and increasing rates of blood glucose and blood pressure (Amarasinghe et al, 2015). In consistent with other studies in Saudi Arabia (Al-Nozha et al, 2004;Al Hayek et al, 2014;Amin et al, 2014) and in many parts of the world (Soegondo et al, 2011;Soriguer, et al, 2012;Xia et al, 2013;Akter et al, 2014;Amarasinghe et al, 2015), our report revealed that individuals with high body weight were more likely to develop diabetes. Excess body fat well documented as being a risk factor for various chronic conditions such as diabetes, hypertension, hyperlipidemia and cardiovascular diseases (Kamadjeu et al, 2006).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Sedantary young people are at risk of obesity, hypertension, diabetes, coronary heart diseases and some types of cancer (Nacar et al, 2014, Amin et al, 2014). In the current study, 64.0% of the students did not perform physical activity lasting at least 30 minutes for five times a week.…”
Section: Discussionmentioning
confidence: 99%